2009
DOI: 10.1021/pr900333h
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Evaluation of Melamine-Induced Acute Renal Toxicity in Rats

Abstract: The recent outbreak of renal failure in infants in China has been determined to be caused by melamine (Mel) and derivatives adulterated in the food. A metabonomic study was performed to evaluate the global biochemical alteration triggered by Mel ingestion in parallel with the acute renal toxicity in rats. Mel at 600, 300, and 100 mg/kg, cyanuric acid (Cya) at 100 mg/kg, and mixture of Mel and Cya (50 mg/kg each) were administered in five groups of Wistar rats, respectively, via oral gavage for 15 days. Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 30 publications
(63 reference statements)
4
66
0
3
Order By: Relevance
“…The mixture used for automatic mass calibration was 200 ng mL -1 of leucine enkephalin (556.3 m/z). The resulting 3-D matrix containing arbitrarily assigned peak index (retention timem/z pairs), sample names (observations), and normalized peak area were exported to SIMCA-P software 11.0 (Umetrics, Umea, Sweden) for multivariate statistical analysis [18][19][20].…”
Section: Uplc-qtof-ms/ms Analysis Of Trichoderma Peptaibolsmentioning
confidence: 99%
“…The mixture used for automatic mass calibration was 200 ng mL -1 of leucine enkephalin (556.3 m/z). The resulting 3-D matrix containing arbitrarily assigned peak index (retention timem/z pairs), sample names (observations), and normalized peak area were exported to SIMCA-P software 11.0 (Umetrics, Umea, Sweden) for multivariate statistical analysis [18][19][20].…”
Section: Uplc-qtof-ms/ms Analysis Of Trichoderma Peptaibolsmentioning
confidence: 99%
“…Furthermore, toxicity included reduced body weight, high blood pressure, epithelial hyperplasia of the urinary bladder and so on (Langman et al, 2009;Xie et al, 2009). However, as the main Ndemethylated metabolites of hexamethylmelamine (Worzalla et al, 1974) which has central nervous system (CNS) toxicity including agitation, confusion, drowsiness, depression and something like epileptic seizure (Legha et al, 1976), melamine may have the CNS toxicity as well.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to arsenic is causally related to a variety of dermal symptoms (arsenicosis), peripheral neuropathy, encephalopathy, bronchitis, pulmonary fibrosis, hepato-splenomegaly, hypertension, peripheral vascular disease, atherosclerosis, cancer (lung, bladder, other organs) and diabetes mellitus (Bolt, 2012). WHO and European Union have set an upper limit of 10 µg/l arsenic in drinking water (Zhao, 2010).…”
Section: Hazardmentioning
confidence: 99%
“…The following studies were identified on arsenic using transcriptomics or proteomics approaches (Robinson et al, 2010a;Hong et al, 2009;Boellmann et al, 2010;Kozul et al, 2009;Zhao et al, 2010). Experiments were performed with mice (4).…”
Section: Hazardmentioning
confidence: 99%